Soil biological attributes in organic coffee farming, pastures and forests in Medium Paraíba River, Fluminense region-RJ, Brazil - Pimentel, Márcio Sampaio; Aquino, Adriana Maria de; Correia, Maria Elizabeth Fernandes; Costa, Janaina Ribeiro; Ricci, Marta dos Santos Freire; De-Polli, Helvécio (Coffee Science - ISSN 1984-3909, 1970)
Soil microbiological attributes and edaphic macrofauna were evaluated with sampling in four seasons of one-year study on six contrasting environments: two coffee cultivars (Coffea arabica L.) with and without crotalaria (Crotalaria spectabilis Roth.) intercroping; pasture and forest. Soil samples were taken in May, August and November, 2002 and February 2003 to evaluate the microbial biomass, basal respiration, metabolic quotient and occurrence of edaphic macrofauna at 0-10 cm deep. Forest soils revealed higher numbers and richer edaphic macrofauna; approximately equal values were observed on coffee environments regardless the presence or not of crotalaria , and pasture soils showed the poorest results. Autumn season was more favorable to microbial mass and to Formicidae, Oligochaeta, Hymenoptera and Heteroptera, while in warmer seasons, spring and summer the Gastropoda, Diplopoda and Homoptera were favoured and the soil metabolic quotient and basal respiration increased. The observed multivariate groups demonstrated that higher organic mather favoured predator and saprophagous species and that higher soil humidity reduced the edaphic macrofauna.